Positive Feedback Improves Students’ Psychological and Physical Learning Outcomes - Ani, Asryan (Universitas Negeri Makassar, 2019)
Abstract. Positive feedback is one of the core strategies used to make educational environment and students’ learning outcomes better. This review aims at revealing the role of positive feedback in improving students’ psychological and physical learning outcomes. Meanwhile, it questions the efficiency of combining positive and negative feedbacks in order to provide better educational experience for students. The findings of the analysis reveal that there is positive relationship between positive feedback and students’ physical and psychological learning outcomes. More specifically, positive feedback is advantageous in increasing students’ motivation, confidence, self-efficacy and academic skills. Furthermore, the study also confirms the benefits of combining positive and negative feedbacks in order to improve students’ learning outcomes and advance their academic skills.